Investigation of Actual In-Plane Geometric Imperfections of Steel Tied-Arch Bridges - Matúš Farbák; Jakub Chromčák; Dáša Bačová; Jaroslav Odrobiňák (Applied Sciences, 2023)
The complex global analysis of the steel tied-arch bridges may require specific data in some cases, e.g., residual stress or real geometrical imperfections. The presented research is focused on the investigation of the actual in-plane shape of the steel tied-arch bridges. To obtain the actual shapes of the arches of existing bridges, 3D terrestrial laser scanning was applied. Data were then investigated as a group in order to find the relationship within the tied-arch bridges’ vertical imperfections. Firstly, the detailed surveyed points in the selected position were mathematically determined to estimate the measured data. The next step included the creation of curves presenting the real shape of the bridges’ arches course using numerical modelling. After the pre-programming, the calculations and related numerical modelling were performed in the Matlab environment. These modelled arch-bridges courses were approximated by using regression analysis. The approximating curves from the regression analysis represent the theoretical course of the arches. The difference between the theoretical shape and the processed measured values may be presented as the examined in-plane imperfections. Subsequently, the paper presents comparisons from the evaluation of the individual imperfections on the investigated bridges and a comparison of the measurement with the standardised shape of the imperfections.